Non-length-dependent small fibre neuropathy. Confocal microscopy study of the corneal innervation. Issue 7 (25th June 2010) - Gemignani, F; Ferrari, G; Vitetta, F; Giovanelli, M; Macaluso, C; Marbini, A
Abstract : Background: It has been recently observed that small fibre neuropathy (SFN) may present as distal symmetrical polyneuropathy and with atypical non-length-dependent pattern. Objective: To describe a small series of patients with non-length-dependent SFN, investigating corneal innervation with corneal confocal microscopy (CCM). Methods: Evaluation of the corneal nerve fibre density using CCM in six women with non-length-dependent SFN. The patients were characterised by sensory disturbance involving proximal regions of the limbs, face and trunks, and the diagnosis was confirmed by the findings of decreased intraepidermal nerve fibre density on skin biopsy. Results: Six women, aged 35–64, had non-length-dependent SFN, related to Crohn disease, impaired glucose tolerance and Sjögren's syndrome, or idiopathic (three cases). In all patients, CCM demonstrated decreased corneal nerve fibre density (12.5–23.4/mm 2 ; normal, >30.6/mm 2 ). Conclusion: Non-length-dependent SFN may represent an intriguing diagnostic problem because of its puzzling presentation and the need for special investigations for its confirmation. In this perspective, CCM may provide a useful, non-invasive tool to complement the diagnostic workup.